In-Silico Study Of The Potential Of Neem Leaf Active Compounds (Azadirachta Indica) As A-Amylase Enzyme Inhibitors Through Molecular Docking And ADMET Analysis - Mutiara Marzalina Wardhani; Tiara Ajeng Listyani; Tatiana Siska Wardani (CV. AFDIFAL MAJU BERKAH, 2026)
Indonesia has reached 20.4 million adults with the fifth highest number of diabetes in the world and is estimated to be 28.6 million by 2050. The use of acarbose has side effects such as digestive problems to potential for the liver and kidneys, so these problems can be overcome with herbal plant treatment, one of which is the active compound of neem leaves (Azadirachta indica). This study aims to analyze the interaction of 20 neem leaf compounds with α-amylase enzymes through the molecular docking approach, ADMET prediction, and modification of potential new compounds as antidiabetic candidates. This research was conducted in silico using PyRx-AutoDock Vina for docking, VegaZZ, PyMOL, and Discovery Studio for optimization and visualization, SwissADME for ADME prediction, and Toxtree for toxicity test. The docking method validation is expressed in RMSD values of <2 Å. The docking results showed that Kaempferol had a ΔGBinding of -7.9 kcal/mol, an RMSD value of 1.229 Å and had a similarity of amino acid residues to the native ligands ASP:197. Kaempferol has a good ADME profile, High (III) category toxicity and is mutagenic and carcinogen. The design of the new compound of Kaempferol i.e. 2-(4-hydroxycyclohexyl)-1-methoxybutane-1,4-diol has amino acid residue similarity to the native ligands ASP A:197, ΔGBinding -5.6, RMSD value 1,704 Å and has good ADME, Low (I) category toxicity. The active compound of neem leaves has the potential to be an inhibitor of the enzyme α-Amylase.